OSH training and workplace accidents at garment industry company sewing unit - Riyani, Tiyas Windi; Mahawati, Eni; Yuantar, MG. Catur (Science Midwifery, 2025)
This study aims to analyze the relationship between OSH training and work accidents in the Sewing Unit of Garment Industry Company. The research employed a quantitative approach with a cross-sectional design, analyzing work accident data from 2022-2024. The research sample consisted of 36 work accident cases occurring during this period. Data collection was conducted through accident record documentation and OSH training records. The results showed that 97.2% of cases fell under the Minor Injury (CR) category, with one case (2.8%) resulting in temporary absence. Statistical analysis revealed a significant relationship between OSH training frequency and workplace accident rates (Risk Ratio = 0.45, 95% CI: 0.28-0.72). Workers attending at least two OSH training sessions annually demonstrated lower injury risks compared to those attending only one session. The anatomical distribution of injuries showed concentration on the left index finger (41.7%) and right index finger (16.7%). This study concludes that increased OSH training frequency positively correlates with reduced workplace accident rates. Key recommendations include implementing more intensive OSH training programs and developing specialized modules focusing on finger injury prevention and ergonomic practices.